Analysis of unsatisfactory results of laparoscopic cholecystectomy in patients with cirrhosis of the liver. - Khimich, S. D.; Muraviov, F. T.; Rudkovska, N. G. (Medicni Perspektivi, 2018)
In the work the analysis of the results of the treatment of 168 patients with complicated cholelithiasis, depending on presence or absence of cirrhosis of the liver has been carried out. In 76 (45.23%) patients, cholelithiasis and concomitant cirrhosis of the liver were complicated, in 92 (54.77%) - complicated cholelithiasis without cirrhosis of the liver. The stage of liver cirrhosis was assessed by the Child-Pugh system. It has been established that cholecystectomy with laparoscopic or traditional open-release in the stage of Child A cirrhosis is quite safe, and the risk of development of complications can be compared with the risk in patients without liver cirrhosis. Urgent surgical interventions in patients with cirrhosis of the liver in the stage of Child B and Child C are associated with an increased risk of development of intra- and postoperative complications and mortality.